Brazil's revolution in commerce : creating consumer capitalism in the American century - Woodard, James P., 1975- (The University of North Carolina Press, 2020)
"James P. Woodard's history of capitalism in Brazil, today the world's fifth most populous country, is at once magisterial, intimate, and penetrating enough to serve as a history of modern Brazil itself. It tells how a modernizing consumer culture and a new economic outlook took hold over the course of the twentieth century, a time when the United States became Brazil's most important trading partner and the tastemaker of its better-heeled citizens"--Provided by publisher